2012
DOI: 10.1089/gtmb.2011.0361
|View full text |Cite
|
Sign up to set email alerts
|

MTHFRPolymorphic Variant C677T Is Associated to Vascular Complications in Sickle-Cell Disease

Abstract: Vaso-occlusion is a determinant for most signs and symptoms of sickle-cell anemia (SCA). The mechanisms involved in the pathogenesis of vascular complications in SCA remain unclear. It is known that genetic polymorphisms associated with thrombophilia may be potential modifiers of clinical features of SCA. The genetic polymorphisms C677T and A1298C relating to the enzyme methylenetetrahydrofolate reductase (MTHFR), a clotting Factor V Leiden mutation (1691G→A substitution of Factor V Leiden), and the mutant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The significant association of FVL mutation with SCD in the present study is consistent with the earlier study of Iranian patients with SCD but inconsistent with the findings of other workers from Africa, Saudi Arabia, Brazil, and Jamaica . Similarly, significant incidence of MTHFR C677T polymorphism among patients with SCD in present series supports to that of the earlier Brazilian studies of patients with SCD . Due to European origin of prothrombin gene, its mutant variants G20210A remain absent in our study.…”
Section: Discussionsupporting
confidence: 52%
“…The significant association of FVL mutation with SCD in the present study is consistent with the earlier study of Iranian patients with SCD but inconsistent with the findings of other workers from Africa, Saudi Arabia, Brazil, and Jamaica . Similarly, significant incidence of MTHFR C677T polymorphism among patients with SCD in present series supports to that of the earlier Brazilian studies of patients with SCD . Due to European origin of prothrombin gene, its mutant variants G20210A remain absent in our study.…”
Section: Discussionsupporting
confidence: 52%
“…A common mutation in 3′-untranslated region of prothrombin gene (G20210A; rs1799963) associated with elevated levels of prothrombin (9). Several studies have investigated the association between vascular complications and FVL, prothrombin G20210A and MTHFR C677T SNPs in SCD patients, but the results are inconclusive (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). As regards to the role of MTHFR C677T in SCD patients, a meta-analysis including 11 cross sectional studies established that MTHFR 677C>T mutation as a high-penetrant risk factor for vaso-occlusive complications (VOC) in SCD patients (20).…”
Section: Lakkakula Vks Bhaskar*mentioning
confidence: 99%
“…All included studies provided data on the prevalence of both FVL and prothrombin G20210A or any one of the mutations in SCD patients with or without VOC. Data on the prevalence of FVL in SCD patients were provided in 10 studies (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and data on the prevalence Figure 1. Schema describing the steps taken during study selection.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…18 In our study FVL was completely absent in both controls and SCD patients as Only wildtype Fv (Figure 7) is dominate and this results approximately compatible with many previous studies which concluded that no significant associations between the SCA and Factor V G1691A (p=0.555). 19,20 and other studies report similar prevalence of FV Leiden in both SCD patients and normal controls (21) suggesting that inherited hyper coagulability risk factors have low impact on the pathogenesis of sickle cell disease and its complications.…”
Section: Discussionmentioning
confidence: 63%
“…24 Meta-analysis showed that the distribution of prothrombin G20210A mutation in SCD patients with or without vasocculsion is similar and revealed that the prothrombin G20210A is not associated with the risk of VOC in SCD patients 14 Other studies reported completely absence of prothrombin mutation and no significant associations between the SCA and prothrombin G20210A mutation. 19,22 In spite that the prevalence of the mutation SCD is variable in different populations but all studies consistent with evidence that it is a risk factor associated strongly with SCD but it's clinical impact differ under many factors with evidence of a gene-gene and geneenvironment interactions which enhance or inhibit gene expression in one side, on other side gene-nutrient interaction play a role in developing the related complications.…”
Section: Discussionmentioning
confidence: 82%